Removal of BOD₅ and COD from Domestic Wastewater by Using a Multi-Media-Layering (MML) System: 10.32526/ennrj/21/20230202 - Al Kholif, Muhammad; Nurhayati, Indah; Sugito, Sugito; Sari, Debby Aroem; Sutrisno, Joko; Pungut, Pungut; Mujiyanti, Dwi Rasy (Environment and Natural Resources Journal, 2023)
This study investigated the ability of the multi-media-layering (MML) to reduce Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) levels in domestic wastewater. MML used in this study is comprised of two MMLs (MML-1 and MML-2) with a total volume for each MML of 0.056 m³. Every MML was filled with gravel media, zeolite, activated carbon, and silica sand. The differences between MML-1 and MML-2 were only found at the height of the media, especially the height of gravel and zeolite media. This study showed that MML-1 had the highest efficiency in reducing BOD₅ (95.47%) and COD (93.10%) compared with MML-2 (BOD₅ of 85.39% and COD of 89.65%). Overall, MML showed promising results in removing pollutants from domestic wastewater. The study also suggested that the height of the gravel media and pH greatly influenced the removal of BOD₅ and COD levels in domestic wastewater.